Cauchy problem for a differential equation in the Banach space with generalized strongly positive operator coefficient - Il'chenko, Yu. V.; Chaikovs'kyi, A. V. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
The concept of strongly positive operator is generalized, and properties of the operators introduced are analyzed. The solutions of the Cauchy problem for a linear inhomogeneous differential equation with generalized strongly positive operator coefficient are found.